2016
DOI: 10.46568/pjass.v4i1.295
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation Of Indicators Of Socio-Economic Deprivation: A Case Study Of The Slums Of Karachi, Pakistan

Abstract: In Pakistan more than one third of its population continues to live below the poverty line (Economic Survey of Pakistan, 2013). Recent research has shown that poverty is wide spread in both urban and rural areas and it is not only rural phenomenon. Since the past few decades, Karachi has experienced an inflow of migrants from all parts of Pakistan in search of better opportunities. Karachi has about 650 katchi abadis (squatter settlements) which are home to 50% of city’s population (Sindh Katchi Abadis Authori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The study's findings also support Omollo (2015), which found a significant effect of monetary rewards on employee performance. In addition, the study's findings also support the conclusions of Mamdani and Minhaj (2016) and Al-Belushi and Khan (2017).…”
Section: Findings and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The study's findings also support Omollo (2015), which found a significant effect of monetary rewards on employee performance. In addition, the study's findings also support the conclusions of Mamdani and Minhaj (2016) and Al-Belushi and Khan (2017).…”
Section: Findings and Discussionsupporting
confidence: 85%
“…Motivation is a process that begins with a physiological or psychological deficiency or need that ignites a behavior or drive targeted at accomplishing a goal or getting a reward (Luthans, 1992). Mamdani and Minhaj (2016) expressed that employee motivational incentive plans are the most commonly used technique in organizations. Motivational incentives include both monetary and non-monetary incentives.…”
Section: Background Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of determination (Adjusted R2) aims to determine how large the percentage of the independent variable is able to explain the dependent variable. The greater the value of the coefficient of determination, the better the ability of the X variable to explain the Y variable (Mamdani & Minhaj, 2016).…”
Section: Methodsmentioning
confidence: 99%